2017
DOI: 10.5604/12321966.1233555
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity vs. simple carbohydrates consumption by elderly people suffering from diseases of the cardiovascular system

Abstract: Introduction. The number of cyclists increases each year. Some people treat cycling as a passion and practice it at every possible occasion, while for others it is a mean of transport or a form of relaxation at the weekend. However, very few people realize that cycling can also have a negative impact on their health. Objective. To assess the prevalence of lower extremity and spine pain in cyclists, and evaluate the influence of various factors causing it. Materials and method. The study was performed on 167 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Those who had a higher intake of refined carbohydrates also had a higher prevalence ratio of obesity; however, the interaction between gender and refined carbohydrates intake showed a negative multiplicative interaction. Some other related studies showed that sweet foods and beverages were significant risk factors for obesity [ 28 , 29 , 30 , 31 , 32 , 33 ]. It was also found in one study that one additional spoonful of sugar consumed every day increased the risk of being overweight and obese by about 14% [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who had a higher intake of refined carbohydrates also had a higher prevalence ratio of obesity; however, the interaction between gender and refined carbohydrates intake showed a negative multiplicative interaction. Some other related studies showed that sweet foods and beverages were significant risk factors for obesity [ 28 , 29 , 30 , 31 , 32 , 33 ]. It was also found in one study that one additional spoonful of sugar consumed every day increased the risk of being overweight and obese by about 14% [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some other related studies showed that sweet foods and beverages were significant risk factors for obesity [ 28 , 29 , 30 , 31 , 32 , 33 ]. It was also found in one study that one additional spoonful of sugar consumed every day increased the risk of being overweight and obese by about 14% [ 33 ]. In contrast, our study did not show a significant association between sweet foods and beverages and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…High sugar consumption in addition to inactive lifestyle is also associated with the higher prevalence of obesity (31). An additional spoon of sugar consumed daily is thought to be associated with 14% increased risk of being overweight or obese (32). Sugars are found to enhance cell proliferation and migration, induce DNA damage, and increase inflammation (33).…”
Section: Discussionmentioning
confidence: 99%
“…7 Kelompok masyarakat yang gemuk dan obesitas memiliki kecenderungan lebih sering mengkonsumsi makanan manis dibandingkan yang kelompok masyarakat yang memiliki berat badan ideal. 8 Yang menarik bahwa asupan lemak jenuh berhubungan dengan penurunan profil VLDL jika asupan karbohidrat terkendali. 9 Asupan makan, aktivitas fisik, perilaku sedentari, dan faktor genetik merupakan beberapa dari sekian banyak kemungkinan penyebab dari obesitas.…”
Section: Pendahuluanunclassified